Sustainable mobility in Europe: Problems in defining and implementing an operational measure - Roger Vickerman (European Regional Science Association (ERSA), 1998)
Transport policy in Europe, both at the European Union level and the national level, has been dominated by the concept of sustainable mobility. This concept is rarely adequately defined, and even more rarely is an operational measure of the concept identified. We know that sustainable mobility is an attempt to relate both the environmental damage and other negative externalities associated with transport, on the one hand, and the positive benefits linked to the role played by an efficient transport system in sustaining and enhancing a given level of activity and its growth in the economy as a whole, on the other hand, to the mobility of both individuals and goods. Sustainability in any system implies that the system is capable of maintaining itself in the long term so that current levels of activity do not damage future prospects. These concepts are well known and broadly accepted, what has proved more difficult is the definition of operational measures in the context of a fully worked through model linking transport, the economy and the environment. This paper attempts to provide such a framework. It argues that sustainability can only be understood in a model which is explicitly spatial, since the distribution of economic activity and of the externalities associated with transport are a key element in the definition of sustainability. The paper provides a framework which synthesises recent work in the new economic geography, in the economics of transport infrastructure and the environmental effects of transport as the basis for a definition of a set of indicators which can be used as tests of the sustainability of transport policy measures.
Keywords: 330